Evaluasi kualitas air limbah domestik sekolah internasional dan fasilitasnya di Tangerang Selatan - Alfarisie, Muhammad Salman (Fakultas Teknik - Universitas Satya Negara Indonesia, 2025)
Improper liquid waste treatment will have a negative impact on the environment and will create a dirty, squalid impression and a strong, foul odor. If that happens, it will certainly disturb the surrounding environment. School liquid waste can also stagnate and usually produces a foul odor and can disturb the comfort of the surrounding community. Evaluation of pollutants is carried out by monitoring pH, BOD, COD, TSS, fatty oil and total coliform. The results obtained show that there is 1 of 8 test parameters that provide results that exceed the environmental quality standards determined by the Regulation of the Minister of Environment and Forestry No. 68 of 2016, it can be concluded that the wastewater is not suitable if it is discharged directly into the receiving water body. For this reason, special attention is needed in handling the Total Coliform microbiological parameters. Improve the quality, quantity and professionalism in monitoring and testing wastewater, especially domestic wastewater.